Tolvaptan in reversing worsening acute heart failure: A systematic review and meta-analysis. Issue 11 (November 2019) - Wang, Lili; Zhang, Qianhui; Liu, Meixia; Chen, Shuxia; Han, Shuang; Li, Jing; Du, Rongpin
Objective: In this meta-analysis, we aimed to compare efficacy and clinical outcomes of tolvaptan in treating acute heart failure (AHF). Methods: Using MEDLINE, we searched relevant clinical studies using tolvaptan that investigated clinical effects in treating AHF. We performed meta-analysis for potentially extractable clinical outcomes such as body weight reduction, change in serum sodium levels, and clinical or safety events including worsening heart failure, worsening renal function (WRF), all-cause mortality, rehospitalization, and dyspnea improvement. Results: The results showed that tolvaptan significantly reduced body weight (mean change: −1.28 kg, 95% credible interval (CI): −1.58–0.98), increased serum sodium levels (mean change: 3.48 mmol/L; 95% Cl: 3.22–3.74), and improved dyspnea function (odds ratio (OR): 1.43; 95% CI: 1.26–1.62) versus conventional therapy. The event risk of WRF was also significantly reduced (OR: 0.35; 95% CI: 0.15–0.80). Low, intermediate, and high tolvaptan doses did not reduce mortality and rehospitalization risks. No significant publication bias was observed regarding effects on mortality and rehospitalization. Conclusion: Current evidence indicates that using tolvaptan as add-on therapy can decrease body weight, increase sodium levels, improve dyspnea function, and reverse WRF, which may circumvent loop diuretics overdose and improve outcomes in patients with AHF.